Randomized double-blind controlled clinical trials with herbal preparations of Serenoa repens fruits in treatment of lower urinary tract symptoms - Görne, Rainer C.; Wegener, Tankred; Reichling, Jürgen (Wiener medizinische Wochenschrift, 2017)
SummaryIn this review, results of randomized double-blind controlled clinical trials (RCTs) with extracts of Serenoa repens fruits at a dose of 320 mg/d for the treatment of lower urinary tract symptoms (LUTS) are assessed. Of the RTCs conducted for up to 6 months, a benefit was seen in three of three RTCs with ethanolic, in eight of nine RTCs with hexane, and in one of two RTCs with CO2 extracts. Of the RTCs conducted for more than 6 months, a benefit was seen in two RTCs with hexane and in one RTC with CO2 extracts, whereas one RTC with an ethanolic, two RTCs with hexane, and one RTC with CO2 extracts did not show positive results. As LUTS are dynamic conditions with strong spontaneous fluctuation over time, the majority of patients might expect improvement of single symptoms and thus of quality of life, particularly as the extracts are well tolerated even in long-term treatment.
Gesehen am 06.04.2018